Comparison of the vitality test with sensitivity tests in mature and immature teeth: clinical trial - Funda Çağırır Dindaroğlu; Narin Özay Güngör (BMC, 2024)
Abstract Background One of the most important steps in deciding on the treatment of a tooth is to determine the vitality and health status of the pulp. Since immature teeth innervation is not completed, the response to sensitivity tests may not yield definite results. Pulse oximetry (PO) which is considered as a vitality test, measures the arterial oxygen saturation (SpO2). This study aims to compare PO, electric pulp test (EPT) and cold test in mature and immature permanent teeth. Methods 20 immature and 20 mature permanent incisors of 6-12-year-old ASA1 children who did not use any analgesics, were included in the study. Pulp vitality of the teeth was determined by EPT, cold test and PO. An infant probe of PO device (CMS60D, Contec Medical Systems Co. Ltd, China) was used to determine the SpO2 of the teeth. The SpO2 level is controlled on the patient's finger by a children's probe and an infant probe of PO. Shapiro-Wilk, Spearman rank correlation test and Kruskal-Wallis test/Dunn post-hoc analysis were used for statistical comparisons. Results There was no significant correlation between finger SpO2 and the mature/immature teeth SpO2 (r=-0.026, r = 0.253). Arterial oxygen saturation values in the immature teeth were significantly higher than in the mature teeth (p = 0.002). There was a high correlation between the vitality response of the EPT, cold test and PO. Conclusions Pulse oximetry can be used as an effective vitality test compared to sensitivity tests in both immature and mature permanent incisors.